SADAR SERVIK: EDUKASI DAN PEMERIKSAAN IVA TEST DALAM DETEKSI DINI KANKER SERVIKS DI DESA BOMAKI KAB. KEPULAUAN TANIMBAR - Kasmiati Kasmiati; Arvicha Fauziah; Kristiova M. Saragih; Jakob L. Jambormias (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Cervical cancer is one of the leading causes of death among women in Indonesia, with the trend of new cases reaching 36,964 cases in 2022. Although the Visual Inspection with Acetic Acid (VIA) method is available efficiently and at low cost, national screening coverage has only reached 10.4%, far below the government target of 80%. This stagnation also occurred in Bomaki Village, Tanimbar Islands Regency, where the non-participation rate in VIA examinations reached 69.81% despite the majority of Women of Reproductive Age (WRA) having higher education and living close to health facilities. This community service activity aimed to improve WRA knowledge regarding cervical cancer and to conduct early detection through the VIA test method. The implementation was carried out in February 2026 at Bomaki Auxiliary Health Center through stages of licensing, material preparation, socialization, VIA test examinations, counseling, and follow-up planning. The results showed that 53 WRA attended the socialization activity and 16 of them were willing to undergo VIA testing. Participant characteristics were dominated by highly educated WRA (87.5%), Tanimbar ethnicity (81.25%), and high levels of psychological acceptance and husband support (75%). However, concerning behavioral risk factors were identified, namely that 87.5% of participants were active smokers and 100% were passive smokers. Of the 16 WRA examined, 13 tested negative (81.25%), 2 had inflammation (12.5%), and 1 tested positive for a precancerous lesion (6.25%). The conclusion of this activity is that education and direct screening were able to encourage WRA participation in early detection, and the examination results obtained have been coordinated with Saumlaki Community Health Center for further management.